Grounding Line Retreat of Denman Glacier, East Antarctica, Measured With COSMO‐SkyMed Radar Interferometry Data. Issue 7 (8th April 2020) - Brancato, V.; Rignot, E.; Milillo, P.; Morlighem, M.; Mouginot, J.; An, L.; Scheuchl, B.; Jeong, S.; Rizzoli, P.; Bueso Bello, J. L.; Prats‐Iraola, P.
Abstract: Denman Glacier, East Antarctica, holds an ice volume equivalent to a 1.5 m rise in global sea level. Using satellite radar interferometry from the COSMO‐SkyMed constellation, we detect a 5.4 ± 0.3 km grounding line retreat between 1996 and 2017–2018. A novel reconstruction of the glacier bed topography indicates that the retreat proceeds on the western flank along a previously unknown 5 km wide, 1, 800 m deep trough, deepening to 3, 400 m below sea level. On the eastern flank, the grounding line is stabilized by a 10 km wide ridge. At tidal frequencies, the grounding line extends over a several kilometer‐wide grounding zone, enabling warm ocean water to melt ice at critical locations for glacier stability. If warm, modified Circumpolar Deep Water reaches the sub‐ice‐shelf cavity and continues to melt ice at a rate exceeding balance conditions, the potential exists for Denman Glacier to retreat irreversibly into the deepest, marine‐based basin in Antarctica. Plain Language Summary: Using satellite radar data from the Italian COSMO‐SkyMed constellation, we document the grounding line retreat of Denman Glacier, a major glacier in East Antarctica that holds an ice volume equivalent to a 1.5 m global sea level rise. The grounding line is retreating asymmetrically. On the eastern flank, the glacier is protected by a subglacial ridge. On the western flank, we find a deep and steep trough with a bed slope that makes the glacier conducive to rapid retreat. If warm water continues to induce high rates of ice melt near the glacier grounding zone, the potential exists for Denman Glacier to undergo a rapid and irreversible retreat, with major consequences for sea level rise. Key Points: SAR observations of Denman Glacier grounding line, East Antarctica, reveal fast retreat of a glacier with a 1.5 m sea level rise equivalent Denman is retreating along a deep trough with a retrograde bed deepening up to 3.5 km below sea level, one of the deepest basin in Antarctica Warm water intrusion in the sub‐ice shelf cavity and the retrograde bed topography makes Denman prone to marine instability in near future